A Randomized Controlled Trial on the Effects of 12 Weeks of Aerobic, Resistance, and Combined Exercises Training on the Serum Levels of Nesfatin-1, Irisin-1 and HOMA-IR - Amanat, Sasan (Front Physiol, 2020)
Background/objective: This study aimed to investigate the impacts of a 12-week training of the aerobic exercise (AE), resistance exercise (RE), and combined exercise (CE) on the serum levels of nesfatin-1, irisin-1 and some other metabolic and anthropometric indices in overweight women with metabolic syndrome. Methods: Sixty overweight women with metabolic syndrome were assigned equally into four groups: aerobic exercise (AE, n = 15), resistance exercise (RE, n = 15), combined exercise (CE, n = 15), and control (n = 15). All groups underwent 12 weeks of intervention. The study variables were measured before and 24 h after the intervention period. Results: Twelve weeks of training resulted in an increase of irisin-1 in the AE and CE groups and nesfatin-1 in all the intervention groups. As expected, all the trained groups exhibited a positive alteration in anthropometric indices and lipid profile in comparison with the control group. Besides, compared with the control group, insulin resistance (based on the homeostatic model assessment) in AE (p = 0.022), RE (p = 0.032), and CE (p < 0.001) groups were reduced significantly. According to the observed changes in the measured indices, serum irisin-1 was significantly correlated with body weight, BMI, body fat percentage, fasting insulin, and HOMA-IR. However, with regard to nesfatin-1, only a negative correlation was observed with body fat percentage and LDL-cholesterol. Conclusions: The 12-week systematic training program changed circulating irisin-1 and nesfatin-1. Also, change in the serum irisin-1 and nesfatin-1 were correlated with the change in glycemic and anthropometric indices in addition to LDL-cholesterol. Also, exercise training significantly reduced fasting insulin and HOMA-IR in all the intervention groups. RCT Registration Code: IRCT20180806040721N2.